Mobilitas Sosial di Unit Pemukiman Transmigrasi (UPT) Arongo (Studi Kasus Petani Transmigran Etnis Jawa dan Petani Lokal Etnis Tolaki) - Sukmawati Abdullah; Nur Isiyana Wianti; Hajat Ahmad Nur (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2015)
The aim of this research is to observe social mobility of Java people as transmigrant community and Tolaki as local people in southeast Sulawesi. This study used qualitative approach, and carried out in January to July 2014. The key informants in this study are six people, Javanese farmers community leaders and local farmers, and javanese transmigrant farmers whose are social climbing mobility (upwar social mobility) and local farmers with social sinking mobility (downward social mobility). Research result show that vertical social mobility of Javanese transmigrant farmers through productions organisations, expertise organizations, and institutional village i.e. cooperative, farmers group and gapoktan, and political organization. Relations of productions on Java farmer and in the status peasant transformed from no land into farmer as land owner. However, the local ethnic has declined on social status through path of the culture system and marriage custom. Research result showed that through individual land ownership local people have easily for buying their land. Relations of productions is change especially for Tolaki people through transmigration program that change the communal land ownership to individual land ownership. Keywords: social mobility, transmigrations, Tolaki, Javanese, UPT. Arongo